Women's Attitudes and Health Beliefs toward Osteoporosis Screening in a Community Pharmacy - Deo, Priyanka (Hindawi Publishing Corporation, 2013)
The aim of this study was to examine women's attitudes and health beliefs towards osteoporosis screening in a community pharmacy setting, utilizing the theoretical framework of Health Belief Model. A nonexperimental, cross-sectional research design, examining a convenience sample of women aged 18 and over, from several New York City senior care centers, a church, and a university campus in New York, was employed to assess the study objectives. Osteoporosis Health Belief Scale questionnaire was used to study the attitudes and health beliefs of participants towards bone mineral density screening in community pharmacy. From the study, it was observed that perceptions of severity and susceptibility towards osteoporosis and subjects' demographic characteristics did not seem to significantly influence the decision to screen in a community pharmacy setting. The perceptions of benefits of community pharmacy-based osteoporosis screening and the perceived barriers were found to be of greater importance in women's decisions to engage in osteoporosis-specific preventive behavior.